2015
DOI: 10.1142/s0218625x15300014
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Behavior of Micro/Nanotextured Surfaces Investigated by Atomic Force Microscope: A Review

Abstract: Tribological issues between friction pair are fundamental problems for minimized devices because of their higher surface-to-volume ratio. Micro/nanotexturing is an e®ective technique to reduce actual contact area between contact pair at the nanoscale. Micro/nanotexture made a great impact on the frictional behavior of textured surfaces. This paper summarizes the recent advancements in the¯eld of frictional behavior of micro/nanotextured surfaces, which are based on solid surface contact in atmosphere environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 109 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…In summary, various factors which affect frictional behavior of a micro/nanotextured surface at the nanoscale can be discussed in detail. For example, density of texture, size of contact area, and shape of texturing structure [14].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, various factors which affect frictional behavior of a micro/nanotextured surface at the nanoscale can be discussed in detail. For example, density of texture, size of contact area, and shape of texturing structure [14].…”
Section: Discussionmentioning
confidence: 99%
“…Surface patterns on textured surfaces usually have regular distributing characteristics at nano- or micro-scales, therefore microscopic analysis is required. Scanning electron microscope (SEM), atomic force microscope (AFM) and laser scanning confocal microscope (LSCM) are often used to observe the geometrical characteristics of surface texture [ 82 , 83 , 84 ]. Additionally, some researchers have paid attention to the residual stresses in surface layers on the textured surfaces [ 85 , 86 ].…”
Section: Surface Texture-based Surface Treatments With Improved Pementioning
confidence: 99%
“…While under the negative effects of friction in normal applications, the service performance of Ti6Al4V engineering components would be decreased and then the lifecycle of the whole equipment might also be reduced [ 100 , 101 ]. Surface texture-based surface treatments developed by different scientists and engineers have provided promising approaches to overcome the relevant issues [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ,…”
Section: Surface Texture-based Surface Treatments With Improved Pementioning
confidence: 99%
“…Surface texturing has been considered as an effective method to improve the friction coefficient and wear rate of friction couples [2][3][4]. Huang et al [5] experimentally investigated the coupling effects of surface texture and surface wettability on contact lubrication of elastomers, it is found that the friction behavior of the surface texture is quite different under different lubrication conditions.…”
Section: Introductionmentioning
confidence: 99%